(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Chronic sinusitis, defined as an inflammatory process that involves the paranasal sinuses and persists for 12 weeks or longer. The conventional treatment is either conservative or surgical. Since this ailment is of a chronic nature, simple conservative management will not be sufficient for a cure. Even though the surgery is effective, there is chance of recurrence and morbidity. The clinical picture of chronic sinusitis shows the predominance of Kaphavata dosha in Jatrurdhwa. Sigru is a single drug having Thikshna ushna guna and Vatakaphahara properties and is included in Sirovirechana group. Arkaprakasa written by Ravana illustrates a large number of Arkas (distillates) which is found to be very effective and harmless and Sigrubeeja Arka nasya indicated in Siroroga was selected for the study. Methods: The study design was interventional pre and post evaluation without control and sample size fixed as 30 patients. The data collection was done with case proforma, symptomatic scoring using VAS scale, Nasal Signs and Symptoms Score (NSSS), and X-ray PNS. Selected patients were subjected to Nasyakarma with Sigrubeeja arka for a period of 7 days. Assessments were done prior to the commencement of intervention and on 15th, 30th, 60th day of follow up. Statistical analysis was done using Wilcoxon Signed Rank test. Result: Change in outcome variables like headache, nasal obstruction, nasal discharge, loss of smell, and postnasal drip, showed significant results. Conclusion: Sigrubeejaarka was found to be effective in chronic sinusitis.